Nanotherapeutics to Modulate the Compromised Micro-Environment for Lung Cancers and Chronic Obstructive Pulmonary Disease - Seshadri, Dhruv R.; Ramamurthi, Anand (Frontiers in Pharmacology, 2018)
The use of nanomaterials to modulate the tumor microenvironment has great potential to advance outcomes in patients with lung cancer. Nanomaterials can be used to prolong the delivery time of therapeutics enabling their specific targeting to tumors while minimizing and potentially eliminating cytotoxic effects. Using nanomaterials to deliver small-molecule inhibitors for oncogene targeted therapy and cancer immunotherapy while concurrently enabling regeneration of the extracellular matrix could enhance our therapeutic reach and improve outcomes for patients with Non-Small Cell Lung Cancer (NSCLC) and Chronic Obstructive Pulmonary Disease (COPD). The objective of this review is to highlight the role nanomedicines play in improving and reversing adverse outcomes in the tumor microenvironment for advancing treatments for targeting both diseases.